Estimasi Volume , Biomassa Dan Karbon Hutan Rakyat Jati Unggul Nusantara Desa Dungus Kecamatan Dagangan Kabupaten Madiun - Rohmatiah, Ahadiati; Lukito, Martin (JURNAL AGRI-TEK, 2015)
The purpose of this study is the potential Wood and plant biomass potential Jati Unggul Nusantara (JUN). and carbon content (C) stored in various organs of plants, and the potential of plantations to absorb CO2. The study was conducted on private forest in the village Dungus JUN plants. District. Kec. Dagangan . Kab. Madiun, through activities in the forest inventore age of five measurements of wet weight of leaves and twigs, stems, branches and leaves made with the technique of